Fabrication of nitrogen-doped porous graphene mesh with improved anodic performance for Li-ion batteries - Teo, Rong Xuan (2017)
Graphene, a form that consists of a single layer from graphite, has attracted heavy attention for its use as the electrode material for electro-chemical energy storage since its first preparation in 2004. This is attributed to its fascinating internal structure, atomic configuration, its electronic properties, overall chemical inertness and the ease of mass production. The novel 2-Dimensional (2D) structure endows graphene with exceptional Lithium (Li)-storage properties since Li ions can be absorbed on both sides of the graphene sheets, resulting in doubling of storage capacity as compared to its graphite counterpart, which possess a limited theoretical capacity of 372 mAh g−1. Studies in recent era demonstrated that the Li-storage performance of graphene is highly dependent on its porous structures and defect sites that are available on the graphene sheets. This thesis aims to fabricate nitrogen-doped porous graphene mesh (NPGM) and investigate its anodic performance on Li-ion batteries. The final product, NPGM, was revealed to strengthen and enhances the Li-ion battery’s properties which provides increased chemical stability and high electrical conductivity. Furthermore, when applied as an electrode, the graphene mesh exhibit high specific capacity (500 mAh g−1 at a current density of 0.2 C), implying its potential usage in electrical applications.